An analysis of the barbell motion depending on its weight in disabled powerlifting - Seidel, W.; Zurowska, A. (Baltic Journal of Health and Physical Activity, 2014)
Background: The aim of the study was to assess the symmetry of flexion and extension movements in upper limbs in disabled powerlifters during bench press with different barbell loads. Material/Methods: 29 disabled athletes from the National Powerlifting Team were examined. Mean age was between 23.9 ± 6.1. Mean sport experience was 5.4 ± 3.6 years. Results: Both flexion and extension movement were performed symmetrically, which was indicated by an insignificant (p < 0.05) difference in the movement onset in the left and the right upper limb. Conclusions: Time differences in the movement onset and the achievement of maximal angular velocity were statistically insignificant in all trials (loads from 40% to 95% 1RM). During extension with loads over 60% 1RM differences in time of achieving maximal angular velocity were statistically significant or close.